Pemberdayaan Masyarakat Dalam Pengelolaan Produk Olahan “Sambal Gurita Octonea” Dari Segi Kemasan Dan Kandungan Gizi Di Kecamatan Labuhan Haji, Kabupaten Lombok Timur - Mulyani, Laily Fitriani; Mukhlis, Alis; Dwiyanti, Septiana (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
One of the products of octopus biota that has been processed in the coastal area of ​​Labuhan Haji District, East Lombok Regency is octopus chili sauce made from octopus biota of the Octopus cyanea type or known as "Octonea Octopus Sambal". Its spicy and savory taste makes this product an alternative that is in great demand by many people because it has nutritional content such as carbohydrates, vitamin C, phenols to antioxidants for the body and can have economic value for the surrounding community. To meet market needs, an attractive packaging technique is needed for a product. So that assistance is needed in packaging the Octonea Octopus Sambal product which is a selling point and its nutritional content is also seen so that the safety of consuming the product is known. This is done as a form of effort to increase added value in marketing a local food product that has nutritional and economic value. The approach method applied in this community service activity is the active participation method, namely by involving coastal women's groups in making Octonea Octopus Sambal product packaging.